The intracellular Ca(2+) release channel TRPML1 regulates lower urinary tract smooth muscle contractility - Griffin, Caoimhin S. (Proc Natl Acad Sci U S A, 2020)
TRPML1 (transient receptor potential mucolipin 1) is a Ca(2+)-permeable, nonselective cation channel that is predominantly localized to the membranes of late endosomes and lysosomes (LELs). Intracellular release of Ca(2+) through TRPML1 is thought to be pivotal for maintenance of intravesicular acidic pH as well as the maturation, fusion, and trafficking of LELs. Interestingly, genetic ablation of TRPML1 in mice (Mcoln1(−/−)) induces a hyperdistended/hypertrophic bladder phenotype. Here, we investigated this phenomenon further by exploring an unconventional role for TRPML1 channels in the regulation of Ca(2+)-signaling activity and contractility in bladder and urethral smooth muscle cells (SMCs). Four-dimensional (4D) lattice light-sheet live-cell imaging showed that the majority of LELs in freshly isolated bladder SMCs were essentially immobile. Superresolution microscopy revealed distinct nanoscale colocalization of LEL-expressing TRPML1 channels with ryanodine type 2 receptors (RyR2) in bladder SMCs. Spontaneous intracellular release of Ca(2+) from the sarcoplasmic reticulum (SR) through RyR2 generates localized elevations of Ca(2+) (“Ca(2+) sparks”) that activate plasmalemmal large-conductance Ca(2+)-activated K(+) (BK) channels, a critical negative feedback mechanism that regulates smooth muscle contractility. This mechanism was impaired in Mcoln1(−/−) mice, which showed diminished spontaneous Ca(2+) sparks and BK channel activity in bladder and urethra SMCs. Additionally, ex vivo contractility experiments showed that loss of Ca(2+) spark–BK channel signaling in Mcoln1(−/−) mice rendered both bladder and urethra smooth muscle hypercontractile. Voiding activity analyses revealed bladder overactivity in Mcoln1(−/−) mice. We conclude that TRPML1 is critically important for Ca(2+) spark signaling, and thus regulation of contractility and function, in lower urinary tract SMCs.